Deadly documents : technical communication, organizational discourse, and the Holocaust : lessons from the rhetorical work of everyday texts /: technical communication, organizational discourse, and the Holocaust : lessons from the rhetorical work of everyday texts. (2016) - Ward, Mark, 1958-
No abstract available